146k views
3 votes
-4(3 - 2x) + 2x = 2x4

User Phentnil
by
5.1k points

1 Answer

3 votes

Answer:

No solution

Explanation:

Knowing the equation -4(3 - 2x) + 2x = 2x(4), we can tell that we need to solve for x.

First, we can distribute out multiplication on both sides:

-4(3 + (-2x)) + 2x = 2x(4)

(-4)(3) + (-4)(-2x) = 2x(4)

-12 + 8x = 8x

Second, we can subtract 8x from both sides:

-12 + 8x = 8x

-12 = 8x - 8x

-12 = 0

This shows that there are no solutions to this equation for x.

User Gaelle
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.